Association between gender-based discrimination and medical visits and HIV testing in a large sample of transgender women in northeast Brazil - Beo Oliveira Leite; Danielle Souto de Medeiros; Laio Magno; Francisco Inácio Bastos; Carolina Coutinho; Ana Maria de Brito; Maria Socorro Cavalcante; Inês Dourado (BMC, 2021)
Abstract Background Gender-based discrimination remains a substantial barrier to health care access and HIV prevention among transgender women in Brazil. The aim of this study was to investigate the association between gender-based discrimination and medical visits, as well as with HIV testing among transgender women in the last 12 months in northeast Brazil. Methods This is a cross-sectional study of 864 transgender women recruited using Respondent-Driven Sampling in three cities in northeastern Brazil in 2016. A socio-behavioral questionnaire was applied. Multivariate analyses were performed using logistic regression, with odds ratio and respective 95% confidence intervals estimation, to estimate the effect of gender-based discrimination on two outcomes: i) medical visits and ii) HIV testing in the last 12 months. Results 547 transgender women (67·0%) had medical visits, and 385 (45·8%) underwent HIV testing in the last 12 months. In the multivariate analysis, gender-based discrimination was associated with a reduced likelihood of medical visits (OR: 0·29; 95%CI: 0·14-0·63) and HIV testing (OR: 0·41; 95%CI: 0·22-0·78) in the last 12 months. Conclusion Gender-based discrimination played an essential role in reducing the access of TGW to medical visits and HIV testing services. Furthermore, by confirming the association between gender-based discrimination and medical visits and HIV testing in the multivariate analysis, we have demonstrated how this predictive variable can affect by reducing access to health services. The findings point to the need for non-discriminatory policies based on the defense and promotion of human rights that may foster the access of transgender women to Brazilian health services.